Diametral Tensile Strength of Microhybrid and Nanohybrid Composite Resins - Jesslyn Nathania Sundiharja Putri; Elline Elline (Journal of Indonesian Dental Association, 2021)
Introduction: Microhybrid and nanohybrid composite resins are commonly used due to their high diametral tensile strength, which indicates the resistance of a material to chewing in posterior tooth restoration. Both composite resins have been widely produced via various modifications of their composition. Objectives: To evaluate the diametral tensile strength of composite resins with microhybrid and nanohybrid fillers. Methods: In this experimental laboratory study, microhybrid (DenFilTM) and nanohybrid (DenFilTM N) composite resins were shaped into 10 specimens each in cylindrical molds (6 mm diameter Ã— 3 mm height) by the bulk-fill technique, and the upper layer was flattened using mylar strips and then polymerized using a light-curing unit for 20 s. Then, composite resin samples were immersed in cell culture plates filled with 2.5 mL of artificial saliva in a 37Â°C incubator for 24 h. Dimensions of the soaked specimens were examined using a digital caliper and tested using a universal testing machine. Results: The diametral tensile strength values for microhybrid and nanohybrid composite resins were 41.67 MPa and 45.42 MPa, respectively. Conclusion: There was no significant difference in the diametral tensile strength of microhybrid and nanohybrid.